The Effect of Ginger Decoction Compress on Pain Reduction in Gout Arthritis Patients - Abdullah, Muhamad Sahid; Hardiansah, Yayan; Rukmana, Fitrihan; Yulandasari, Vera (Balai Publikasi Indonesia, 2026)
Gout arthritis is a prevalent inflammatory joint disease characterized by hyperuricemia and deposition of monosodium urate crystals in the joints, leading to acute pain and impaired mobility. Conventional management primarily relies on pharmacological therapy such as non-steroidal anti-inflammatory drugs (NSAIDs). While effective, long-term use of these drugs carries risks of gastrointestinal bleeding, renal impairment, and cardiovascular complications. This underscores the need for non-pharmacological alternatives that are safe, cost-effective, and culturally adaptable. Ginger (Zingiber officinale) contains bioactive compounds—gingerol, shogaol, and zingerone—that exhibit anti-inflammatory and analgesic properties. This study aimed to evaluate the effectiveness of ginger decoction compress in reducing pain among patients with gout arthritis in Sunggaling Hamlet. A quasi-experimental two-group pretest-posttest design was applied, involving 44 purposively selected participants. The intervention group (n = 22) received ginger decoction compresses for three consecutive days, while the control group (n = 22) received standard care. Pain intensity was measured using the Visual Analog Scale (VAS). Data were analyzed using paired and independent t-tests with a significance level of p < 0.05. Results showed a significant reduction in pain intensity in the intervention group (from a mean VAS score of 7.2 to 3.1, p < 0.05), whereas the control group showed no meaningful change. These findings support the use of ginger decoction compress as a complementary nursing intervention for pain management in gout arthritis patients.